The Influence of Knowledge, Skill, Attitude, and Professionalism on the Individual Performance of Bankers, Lecturers, Teachers and Nurses in Jabodetabek - Muchtamim (Journal of Research in Business, Economics, and Education, 2021)
This study aims to examine and analyze the influence of Knowledge, Skill, Attitude, and Professionalism on the Individual Performance of a banker, Lecturer, Teacher and Nurse in Jakarta, Tangerang, and Bekasi. Data collection was carried out by distributing questionnaires with a sample size of 100 respondents. and using a quantitative descriptive approach. Submission of the questionnaire is done inline via google meet. The data analysis used was statistical analysis in the form of validity test, reliability test, classical assumption test, and multiple linear regression. The results of this study indicate that the data under study are all valid and reliable. Furthermore, the multicollinearity test shows that there is no multicollinearity, this is evidenced by the VIF of each independent variable <10 with a tolerance above 10%. The data is normally distributed and there is no heteroscedasticity with the scatterplot points with a regular pattern, narrowing, widened or wavy. Partially and simultaneously the variables Knowledge, Skill, Attitude, and Professionalism affect individual performance. This is evidenced by the results of the T test and F test which also show the significant value of the two independent variables that support the hypothesis. In the determination test, the influence variable of the independent variable on the dependent variable is Knowledge contributes 35.3%. Skill contributes 34.9% influence, Attitude contributes 52.4% influence and Professionalism contributes 48.1% influence. In the autocorrelation test, it is known that autocorrelation does not occur, this can be seen from the DW of 1,651 which is in the range -2 and 2.